Accounting for Small Manufacturers (Book). - Burns, Thomas J.; Gray, O. Ronald (The Accounting Review, 1981)
Abstract Reviews the book "Accounting for Small Manufacturers," by C. Richard Baker and Rick Stephan Hayes.